Choosing to Stay: Alternate Migration Decisions of Ghanaian Youth - Setrana, Mary (2021)
This article focuses on nationals from Ghana who have lost interest in pursuing migration dreams to Europe and North America after failed attempts to migrate. Many less experienced youths who attempt to migrate to Europe and North America face challenges such as strict immigration laws, high cost of financing migration plans, or illegal recruiters. Some risk their lives through dangerous routes to achieve their migration goals. The negative consequences recorded are numerous, including death en route to Europe and North America. Using life stories, this article lets failed migrants recount the frustration, wasted resources and years spent to fulfil their migration dreams. It discusses individual factors such as experiences that affect the decision not to pursue migration dreams despite the culture of migration in their communities. The article concludes that strict immigration policies in Europe and North America have restricted international migration among less experienced and less skilled youth in Ghana, leading to personal decisions not to migrate but adjust to the conditions at home, and later describing their stay as a preferred decision.